Study of Characteristics of Sweet Pepper Varieties and Hybrids Recommended for Cultivation in Protected Lands - qizi, Gafurova Mashhura Saidulla (European Journal of Life Safety and Stability (2660-9630), 2023)
Sweet pepper (Latin Capsicum annuum) is an annual herb native to Central America (Mexico, Guatemala). Since sweet pepper is a valuable vegetable crop, its demand has always been high. In the conditions of Uzbekistan, the correct selection of varieties and hybrids is the guarantee of an abundant harvest in order to obtain a quality harvest from sweet pepper. 8 local varieties of sweet pepper are included in the State Register of agricultural crops recommended for planting in the territory of the Republic of Uzbekistan. This paper provides information on the morphological characteristics and characteristics of sweet pepper varieties and hybrids grown in protected areas.